2022
DOI: 10.5014/ajot.2022.049202
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Service Delivery Among Medicaid-Enrolled Children and Adults on the Autism Spectrum and With Other Intellectual Disabilities

Abstract: Importance: Rates of occupational therapy service utilization among people with autism spectrum disorder (ASD) or intellectual disability (ID) have not been explored in population-based samples. Objective: To describe occupational therapy services delivered to Medicaid-eligible persons younger than age 65 yr identified as having ASD, ID, or both and to evaluate demographic factors associated with occupational therapy service utilization in this population. Design: Retrospective, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Other notable aspects of the work not included in Table 1 capture issues of diversity and representation. Seven studies included an explicit focus on issues of equity based on race, ethnicity, gender, and income (Benevides et al, 2022; McGhee Hassrick et al, 2021; Roux et al, 2022; Schott et al, 2022a; Shattuck et al, 2020; Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022). One review article noted that under‐represented study participants included autistic individuals who were women, transgender, non‐White, low income, and those with intellectual disability or with minimal speaking communication (McGhee Hassrick et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other notable aspects of the work not included in Table 1 capture issues of diversity and representation. Seven studies included an explicit focus on issues of equity based on race, ethnicity, gender, and income (Benevides et al, 2022; McGhee Hassrick et al, 2021; Roux et al, 2022; Schott et al, 2022a; Shattuck et al, 2020; Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022). One review article noted that under‐represented study participants included autistic individuals who were women, transgender, non‐White, low income, and those with intellectual disability or with minimal speaking communication (McGhee Hassrick et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In regard to the main findings of individual ATRP‐funded studies, results verified high rates of co‐occurring health and mental health conditions beginning in adolescence and use of polypharmacy (Kerns et al, 2020; Rast et al, 2021), along with utilization of emergency department and inpatient hospitalizations often related to psychiatric diagnoses (Rast et al, 2022; Schott et al, 2022b). Studies documented how autistic youth are less likely to have their health and mental health needs met or to have positive care experiences (Fernandes et al, 2021; Roux et al, 2022), and how drop‐offs in utilization of some services (speech therapy, occupational therapy, one‐on‐one supports) begin as early as high school (Benevides et al, 2022; Song, Salzer, Nonnemacher, & Shea, 2022). While case management and mental health service use increased in young adulthood, unmet service needs also increased during this period (Song, Salzer, Nonnemacher, & Shea, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two articles in this special issue focus on the utilization of occupational therapy services among specific populations to advance knowledge in this area. Benevides et al (2022) explored utilization of occupational therapy services among children and adults covered by Medicaid who are on the autism spectrum, have intellectual disability, or both. Their study found lower utilization of occupational therapy services among adolescents and adults compared with younger children and points to potential disparities in access to care by age, race and ethnicity, sex, and urbanicity.…”
mentioning
confidence: 99%